Neuropsychology of Illiteracy - M. Rosselli (Behavioural Neurology)
It is proposed that analysis of illiteracy can not only discern the influence of schooling background on neuropsychological test performance, but also contributes to obtaining a better understanding about the cerebral organization of cognitive activity. Brain organization of cognition, and cognitive sequelae of brain pathology in illiterates are reviewed. It is concluded that: (1) cognitive abilities, as measured by standard neuropsychological tests, are significantly influenced by schooling background; and (2) educational and cultural variables may affect the degree (albeit, not the direction) of hemispheric dominance for language, and other cognitive abilities. A more bilateral representation of cognitive abilities in illiterates is hypothesized.